(untitled) (Quest Journal of Management and Social Sciences, 2024)
Background: Conflict is an inevitable aspect of any organization, including the banking sector, where disagreements between parties, such as between superiors and subordinates, are common. Effective negotiation is often key to resolving these disputes, ensuring mutual satisfaction through discussion and compromise. Objective: This study aims to critically evaluate the negotiation strategies used by management in the commercial banking sector of Kathmandu Valley for conflict resolution. Method: A survey was conducted to gather data on negotiation strategies used by managers in the banking sector for conflict resolution. Participants were selected through purposive sampling, a non-probability sampling method, resulting in a total of 267 respondents, including managers and officers. The collected data were then analyzed using Structural Equation Modeling (SEM) to identify the preferred negotiation strategies and their effectiveness in conflict resolution. Result: The findings indicate that the majority of respondents, who are managers, prefer cooperative strategies in conflict situations, reflecting a high concern for others. The integration strategy was the most commonly used approach for negotiation, demonstrating a focus on maintaining positive relationships while resolving disputes. Conclusion: The study concludes that managers in the Kathmandu Valley banking sector prioritize maintaining good relationships during conflict resolution. This approach reflects a broader strategy of using negotiation to achieve mutually beneficial outcomes. The study provides valuable insights into current practices and offers recommendations for enhancing conflict resolution strategies in Nepal’s commercial banking sector, contributing to smoother operations and greater employee and employer satisfaction. Paper Types: Research Paper Keywords: Negotiation, conflict resolution, structure equation modeling, integrative strategy, compromising strategy, avoiding strategy JEL Classification: F51, D74, G21, C1, C5